Effects of a direct fed microbial (dmf-4) and in-feed antimicrobials on pig performance in a commercial finishing facility - Main, R.G.; Goodband, Robert D.; Tokach, Michael D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 1,000 barrows were used in a 98-day trial conducted in a commercial research facility to determine the influence of a direct fed microbial with and without intermittent treatments of oxytetracycline (OTC) at 400 g/ton. The direct fed microbial was compared to a negative (no feed antimicrobial) and positive control (bacitracin methylene diasalicylate (BMD) at 30 g/ton, alternated with intermittent treatments of OTC at 400 g/ton). No significant differences between the four treatments were observed for any of the growth, efficiency, or carcass parameters evaluated. These results suggest that further work in quantifying the effects of routinely utilizing in-feed antimicrobials in the finishing period is warranted.
Keywords: Swine; Microbial; Antimicrobial; Finishing pigs